Anti-Cancer Activity of Rhizome of Emprit Ginger (Zingiber officinale Rosc.) and Tiwai Onion (Eleutherine palmifolia) through Apoptosis Induction and Cell Cycle Arrest: A Review - Aisyah Nur Salsabilan; Annisa Khumaira; Ika Afifah Nugraheni (Indonesian Society for Cancer Chemoprevention, 2025)
Cancer is a disease caused by the abnormal growth of cells and tissues. One of the main therapeutic approaches for cancer is chemotherapy. The use of plants as an alternative treatment is considered quite relatively effective and efficient. Emprit ginger (Zingiber officinale Rosc.) and tiwai onion (Eleutherine palmifolia) are plants that have potential anticancer properties due to their active compounds. The purpose of this literature review is to examine the various uses of these active compounds and their mechanisms of action as anticancer agents, both in vitro and in vivo, from emprit ginger and tiwai onion. The results of this literature review indicate that emprit ginger contains active compounds, namely gingerol (6-gingerol and 10-gingerol), shogaol (4-shogaol, 6-shogaol, and 10-shogaol), and paradol, which have anticancer activity. Similarly, tiwai onion contains active compounds, namely flavonoids (isoliquiritigenin), polyphenols (oxyresveratrol), and naphtoquinones (elecanacin, eleutherin, eleutherol, eleutherinol, eleutherinon, eleuthoside B, eleutherinoside A), which have anticancer activity. Pre-clinical in vitro and in vivo studies show that emprit ginger and tiwai onion have anticancer activity, including the inhibition of cancer growth through modulation of cell signaling pathways, induction of apoptosis, and cell cycle arrest.Keywords: anticancer activity, apoptosis, cell cycle arrest, emprit ginger (Zingiber officinale Rosc.), tiwai onion (Eleutherine palmifolia).